In Silico Study of Leishmania donovani α-β Tubulin and Inhibitors. (1st July 2014) - Assis, Tamiris M.; Mancini, Daiana T.; Ramalho, Teodorico C.; da Cunha, Elaine F. F.
Abstract : Leishmania donovani is a parasite that causes visceral leishmaniasis, a severe form of leishmaniasis that affects vital organs. An important target for the treatment of this disease is the protein α - β tubulin, which was modeled in this paper and proposed as a target for the treatment of visceral leishmaniasis. Two classes of compounds were studied, dinitroanilines and oxadiazoles. According to the docking results, dinitroanilines interact better with the L loop domain and oxadiazoles interact better with the colchicine domain.